Multidrug-resistant Intestinal Staphylococcus aureus among Self-medicated Healthy Adults in Amassoma, South-South, Nigeria - Onanuga, Adebola; Temedie, Tarilate C (Journal of Health, Population and Nutrition, 2011)
Multiple antibiotic resistant Staphylococcus aureus is one of the common causes of severe nosocomial infections, and the gastrointestinal tract is an important source of its transmission. This study assessed the previous usage of antibiotics by healthy adults (university students and villagers) in Amassoma, Nigeria, and investigated the antimicrobial resistance patterns of their intestinal S. aureus isolates. A questionnaire was used for evaluating the previous usage of antibiotics by the volunteers. Stool samples were collected and cultured, and S. aureus isolates were confirmed using standard microbiological protocols. Their antimicrobial resistance patterns were determined using disc-diffusion and agar dilution techniques. In total, 54 (45.0%) volunteers used antibiotics on self-medications, and the practice was significantly higher (p=0.01) among the villagers than among the students. The level of judicious use of prescribed antibiotics was significantly higher (p=0.003) among the students than among the villagers. Thirty-eight (31.7%) healthy adults were colonized with intestinal S. aureus. The percentages of resistance of the isolates to some antibiotics were as follows: ampicillin–68.4%, doxycycline–60.5%, cefoxitin–34.2%, vancomycin–36.8%, erythromycin–34.2%, and gentamicin–5.3%. Twenty-five (65.8%) of the isolates were multidrug-resistant. The need for sound education on the appropriate use of antibiotics and the importance of proper personal hygiene as means of controlling the spread of bacterial antibiotic resistance are highlighted. Thus, effective strategies in these areas are strongly recommended. Key words: Antimicrobial agents; Drug resistance, Microbial; Gastrointestinal tract; Self-medication; Staphylococcus aureus; Nigeria DOI: http://dx.doi.org/10.3329/jhpn.v29i5.8898 JHPN 2011; 29(5): 446-453